KOMUNIKASI PEMERINTAH KELURAHAN DALAM MENUNJANG EFISIENSI PELAYANAN ADMINISTRASI MASYARAKAT: KASUS DI KELURAHAN SUMBER SARI, KOTA TANJUNGBALAI - Herawati, Tetty; Priadi, Ribut (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study aims to analyze the role of village government communication in supporting the efficiency of public administration services in Sumber Sari Village, Tanjungbalai City. Good communication between the village government and the community is a key factor in improving the quality of fast, precise, and effective administrative services. This study uses a qualitative approach with a case study method to explore in-depth information about communication practices implemented in Sumber Sari Village and their impact on the efficiency of administrative services. The results of the study indicate that transparent, accurate, responsive, and technology-based communication is very important to improve the efficiency of administrative services at the village level. The preparation of a more inclusive communication strategy can accelerate the process of administrative services, reduce administrative errors, and increase public satisfaction.